Underpricing or Overvaluation? Theoretical Review of Initial Public Offering Phenomenon - Yusup, Adi Kurniawan (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 4, 2022)
The abnormal initial return of Initial Public Offerings (IPOs) has become an interesting financial phenomenon that attracts many researchers’ interest. This phenomenon has become more attractive because IPOs have increased during the pandemic since 2021. This study investigates whether the positive initial performance of IPO stock led to underpricing or overvaluation in a broader context in the form of literature reviews. After elaborating and analyzing several related studies, theories and empirical research in the literature, this research finds that the aftermarket has a lower performance than the initial one. It shows that abnormal initial returns tend to be caused by investors’ overvaluation and overreaction instead of underpricing.